The Dynamics Influencing Progress Towards Responsible Investment: A Process Study of the Agency of the Code for Responsible Investment in South Africa (CRISA) - Feront, Cecile (Stellenbosch : Stellenbosch University, 2016)
Thesis (MPA)--Stellenbosch University, 2016.